Molecular approach to the identification and phylogenetic relationship among actinopterygii using mitochondrial DNA 12S rRNA, 16S rRNA and cytochrome B genes in Peninsular Malaysia - Samrah, Siti Farah Quraishia (2018)
The morphological based method has been utilised to identify and classify fish species. However, this method is lacking genetic information which makes it less useful in phylogenetic studies. The present study utilises mtDNA markers namely 12S rRNA, 16S rRNA and cytochrome b genes to characterize, identify the polymorphism and genetic relationship among marine fish species. The genetic relationship among the selected marine fish species was inferred through phylogenetic trees using Neighbor-joining (NJ), Maximum parsimony (MP) and Maximum likelihood (ML) methods. The result showed that 12S rRNA gene was more conserved than 16S rRNA and cytb genes based on the polymorphisms reported. The finding also revealed that Nemipterus nemurus exhibits the highest number of polymorphisms indicating that this species might have experienced the most changed events and thus possessing the most genetic deviation from the common shared ancestry. All the phylogenetic trees that were constructed based on 12S rRNA, 16S rRNA and cytochrome b genes showed a similar clustering with slight differences in their bootstrap values. Some species with greatly morphological resemblance such as Liza macrolepis and Liza vaigiensis however, showed a genetically distant relationship. Nevertheless, another morphological resemblance species namely Pampus argenteus / Pampus chinensis and Drepane longimana / Drepane punctata were consistently observed in all topologies with high bootstrap support (97-100%). Having a distinctive morphological, the Megalaspis cordyla and Caranx sexfasciatus occupied a highly similar nucleotide sequences and showed a consistent clustering in all topologies. This study also revealed that the combined genes provide a better resolution for all phylogenetic trees. Overall, these findings showed that the molecular based method using mtDNA genes were successfully applied to study the diverse Malaysia marine fish species in class Actinopterygii.